Combination of ultra‐performance liquid chromatography‐quadrupole time‐of‐flight mass spectrometry and network pharmacology to reveal the mechanism of Shengyu Decoction for treating anemia. Issue 3 (11th December 2022) - Hu, Yu; Sun, Hui; Yan, Guangli; Zhang, Xiwu; Guan, Yu; Li, Dan; Wang, Xijun
Abstract : Anemia is a common clinical hematological disease with a high incidence, which seriously affects human health. Shengyu Decoction is often used in the treatment of anemia. However, the pharmacodynamic substance basis and therapeutic mechanism are still unclear, which hinders the comprehensive development and utilization of Shengyu Decoction. In this study, 143 compounds were identified in Shengyu Decoction using high‐throughput ultra‐performance liquid chromatography‐quadrupole time‐of‐flight mass spectrometry, 24 of which were absorbed into the blood. Taking these blood‐entering ingredients as the research object, we found through network pharmacology research that ferulic acid, calycosin, and astragaloside A can act on AKT1, MAPK1, and MAPK14, and play a role in treating anemia through PI3K‐Akt signaling pathway and Pathways in anemia. Finally, it was demonstrated that the active compound could bind to the core target with good affinity by molecular docking. The research shows that Shengyu Decoction has multi‐component, multi‐target, and multi‐channel effects in the treatment of anemia, which provides a basis for the development and clinical application of Shengyu Decoction.